Effective Strategies to Improve Qur'an Memorization Quality Through Puzzle Media in Grade X Madrasah Aliyah Al-Wardah Tembung - Fitri Wahyuni (Jurnal Pendidikan Islam, 2025)
The Qur’an is the primary source of Islamic teachings, and memorization (tahfidz) is regarded as a noble practice, yet traditional repetition methods often diminish motivation and limit comprehension. This study investigates the effectiveness of Qur’an puzzle media as an innovative strategy to enhance memorization quality, employing a mixed-methods descriptive-analytical approach through field research at MA Al-Wardah, Tembung. Data were collected via observation, interviews, and documentation using structured instruments, and analyzed using Miles and Huberman’s model of data reduction, data display, and conclusion drawing. Credibility was ensured through triangulation, member checking, and peer debriefing to maintain validity, reliability, and objectivity. The findings reveal that using puzzle media improved students’ memorization accuracy, fluency, and understanding of makhraj and tajweed, while also boosting motivation, concentration, and enthusiasm, thereby making tahfidz more interactive and enjoyable. Overall, this research highlights Qur’an puzzle media as an innovative pedagogical model integrating cognitive, affective, and kinesthetic learning aspects, offering practical insights for teachers and policymakers in developing engaging tahfidz programs and laying a foundation for future studies in Islamic education innovation.